Induction of Type C Viruses in Cultured Guinea Pig Cells - Nayak, D. P. (1973)
Particles morphologically resembling type C viruses were activated by bromodeoxyuridine (BUdR; 10(−4) M) treatment of cultured guinea pig cells. Virus particles were isolated from the cells of normal and leukemic strain 2 and random-bred guinea pigs (adult and embryonic). Immature virus particles with electron-lucent cores were found in the cytoplasmic matrix. The mature particles with electron-dense cores were found outside the cells and some appeared in the process of budding from the plasma membrane. The peak of virus production was observed within 4 days of BUdR treatment. When compared to the amount of virus produced in darkness, visible light enhanced virus production, whereas exposure of BUdR-treated cells to UV light either had no effect or inhibited virus production. Virus particles had a density of 1.16 gm/ml, possessed an oncornavirus-specific reverse transcriptase, and contained a large-molecular-weight RNA (65-70S) which dissociated into 36S subunits after heat denaturation. The BUdR-activated virus particles, therefore, possessed the morphological, biophysical, and biochemical characteristics of type C oncornaviruses.